2014
DOI: 10.1016/j.physletb.2014.01.050
|View full text |Cite
|
Sign up to set email alerts
|

Isospin properties of electric dipole excitations in 48Ca

Abstract: Two different experimental approaches were combined to study the electric dipole strength in the doubly-magic nucleus 48Ca below the neutron threshold. Real-photon scattering experiments using bremsstrahlung up to 9.9 MeV and nearly mono-energetic linearly polarized photons with energies between 6.6 and 9.51 MeV provided strength distribution and parities, and an (\alpha,\alpha'\gamma) experiment at E_{\alpha}=136 MeV gave cross sections for an isoscalar probe. The unexpected difference observed in the dipole … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
64
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 57 publications
(68 citation statements)
references
References 51 publications
(136 reference statements)
3
64
1
Order By: Relevance
“…In a simple macroscopic picture, a displacement of center-of-mass and center-ofcharge of the nucleus generates a vibrational motion trying to restore the proton-neutron symmetry. Nowadays, the rapidly increasing number of experiments using different probes and techniques allow for systematic studies of the PDR over isotopic and isotonic chains from different mass regions [4,[7][8][9][10][11][12][13][14][15][16][17]. A close connection between * derya@ikp.uni-koeln.de the total PDR strength and the amount of the neutron excess of neutron-rich nuclei which on the other hand is correlated with the neutron skin thickness was proposed [6,[18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…In a simple macroscopic picture, a displacement of center-of-mass and center-ofcharge of the nucleus generates a vibrational motion trying to restore the proton-neutron symmetry. Nowadays, the rapidly increasing number of experiments using different probes and techniques allow for systematic studies of the PDR over isotopic and isotonic chains from different mass regions [4,[7][8][9][10][11][12][13][14][15][16][17]. A close connection between * derya@ikp.uni-koeln.de the total PDR strength and the amount of the neutron excess of neutron-rich nuclei which on the other hand is correlated with the neutron skin thickness was proposed [6,[18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…A key issue for the interpretation of the nature of the PDR states is the determination of their isospin character. In this connection extensive work [8][9][10][11][12][13] was made using the (α,α ) reaction, having a strong isoscalar character, and the general result is the presence of different excitation pattern as compared with that of the (γ,γ ) reaction. More recently, experiments performed for the nuclei 208 Pb [14], 124 Sn [15], and 140 Ce [16] to study the E1 and E2 transitions in the region 4-9 MeV have shown that the ( 17 O, 17 O γ ) reaction is a good tool to investigate the isospin properties of these states.…”
Section: Introductionmentioning
confidence: 99%
“…This mode of excitation was first observed in neutron-capture reactions [1]. Nowadays this mode has been found as a non-statistical enhanced dipole strength below the neutron-separation energy for isotopes ranging from light nuclei (8≤Z≤40) up to lead isotopes including the transitional nuclei [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. A series of nuclear experiments have shown that this is a common mode in N=82 semi-magic 136 Xe, 138 Ba, 140 Ce, 142 Nd and 144 Sm nuclei at excitation energies between 5-8 MeV [2,4,5,10].…”
Section: Introductionmentioning
confidence: 99%